Verification of Concurrent Programs with Chalice - Leino, Rustan; Müller, Peter; Smans, Jan (Foundations of Security Analysis and Design V, 2009)
A program verifier is a tool that allows developers to prove that their code satisfies its specification for every possible input and every thread schedule. These lecture notes describe a verifier for concurrent programs called Chalice. Chalice’s verification methodology centers around permissions and permission transfer. In particular, a memory location may be accessed by a thread only if that thread has permission to do so. Proper use of permissions allows Chalice to deduce upper bounds on the set of locations modifiable by a method and guarantees the absence of data races for concurrent programs. The lecture notes informally explain how Chalice works through various examples.